Metoda Video-feedback Intervention to promote Positive Parenting and Sensitive Discipline (VIPP-SD) w pracy terapeutycznej z rodzicami dzieci z grupy ryzyka rozwojowego - Kopeć, Danuta; Kubiak, Hanna (Studia Edukacyjne, 2020)
Video-feedback Intervention to promote Positive Parenting and Sensitive Discipline (VIPP-SD) is a therapeutic intervention based on video-feedback which aims to support positive parenting and sensitive parental discipline. It is a part of evidence-based therapeutic interventions, which means that the effectiveness of the training has been confirmedin rigorously planned and carried out studies of both the general population and various clinical groups. The theoretical framework for VIPP-SD is attachment theory and coercion theory. The basic principle of intervention is referring to family resources in the therapeutic work, primarily in situations in which the correct course of a child’s development can be disturbed by both biological and environmental factors. The article presents the aspects of the application of VIPP-SD in the following clinical groups: families with children at risk of improper development, families in which the functioning of parents creates the development risk for children, and the family environment as a risk factor for children’s development.